Home Electric Power Monitoring System Based on Internet of Things Using the Telegram Application - Prastyo, Okik Dwi; Maulindar, Joni; Nurchim, N (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Work and human needs are very dependent on the presence of electrical energy, especially for household needs. Human negligence in using electrical energy will lead to wasteful use of electrical energy which causes payments to soar among households. Research was conducted to examine the application of monitoring the electrical power used by the device remotely via an internet connection. The system can be implemented using a NodeMCU ESP32, PZEM-004T sensor, 16x2 LCD, and the Telegram application as the system user interface on a smartphone. To be able to monitor via the Telegram application the user must be connected to the internet and the microcontroller must be connected to the internet network. This system using the internet network will make it easier to monitor the electrical power of electronic devices in the home every day. The result of this research is that an Internet of Things-based home electrical power monitoring system using the Telegram application can help and make it easier for home owners to monitor electrical power when the home owner is not at home.